Poly-γ-Glutamic Acid Attenuates Angiogenesis and Inflammation in Experimental Colitis - Munkhtugs Davaatseren; Jin-Taek Hwang; Jae Ho Park; Myung-Sunny Kim; Shuaiyu Wang; Mi Jeong Sung (Mediators of Inflammation)
Poly-γ-glutamic acid (γ-PGA), naturally secreted from various strains of Bacillus, has anti-inflammatory activity. In inflammatory bowel disease (IBD), inflammation is promoted and sustained by angiogenesis; however, the role played by γ-PGA in this condition is unclear. Therefore, we evaluated γ-PGA effects on angiogenesis and inflammation in a dextran sulfate sodium- (DSS-) induced mouse colitis model. Experimental colitis was induced in male C57BL/6 mice by administering 3% DSS. Disease activity index (DAI), histopathological scores, microvascular density, myeloperoxidase activity, and VEGF-A and VEGFR2 expression were compared among control mice, DSS-treated mice, and mice receiving 3% DSS along with γ-PGA at 50 mg/kg body weight per day or 3% DSS with γ-PGA at 200 mg/kg body weight per day. We found that γ-PGA significantly attenuated weight loss, DAI, and colon shortening. γ-PGA also significantly reduced histopathological evidence of injury. Moreover, γ-PGA significantly attenuated DSS-induced blood vessel densities. Furthermore, γ-PGA attenuated DSS-induced expression of VEGF-A and its receptor, VEGFR2. In addition, γ-PGA treatment led to reduced recruitment of leukocytes to the inflamed colon. Therefore, our results indicate that γ-PGA has potential application in conditions marked by inflammatory-driven angiogenesis and mucosal inflammation.